PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETIL ASETAT BUAH OKRA HIJAU (Abelmoschus esculentus L.) - Rahmi , Rahmi Muthia; Fatmawati, Fatmawati; Hidayatullah, M. Hidayatullah; Putri, Putri Indah Sayakti; Aditya, Aditya Noviadi Rakhmatullah (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
Abstract. Okra fruit (Abelmoschus esculentus L.) is a potential medicinal plant because it contains several compounds such as alkaloids, phenols, flavonoids, steroids and tannins which have anti-diabetic, antioxidant, antimicrobial, antiallergic, antiviral and anti-inflammatory properties. The purpose of this study was to identify the content of flavonoid compounds qualitatively and quantitatively. The extraction method was maceration, used ethyl acetate solvent. Qualitative testing of flavonoid compounds used TLC, 5% AlCl₃ spotting appearance. Quantitative test used UV-Vis Spectrophotometry method, quercetin as comparison, λmaks 415 nm. The TLC results show three stains with each Rf value of 0.76; 0.53; 0.23. The results of determined the total flavonoid content of okra fruit were 4.069 ± 0.211 mg QE/g extract. From the research results obtained, it can be concluded that the ethyl acetate extract of green okra contains flavonoids. Kata Kunci: Abelmoschus esculentus L; total flavonoid content; ethyl acetate extract; TLC